How the price of different breeds of feeder cattle has changed over time - F.K. Brazle; J.R. Mintert; J. III Sartwelle; R.P. Jr. Bolze; Ted C. Schroeder (Kansas Agricultural Experiment Station Research Reports, 1995)
Data on feeder steer characteristics, breeds, and prices were collected in 1986/87 and 1993 at Kansas and Missouri feeder cattle auctions to identify changes in buyers' preferences for various breeds. Results from models of feeder steer price/characteristics indicate that the relative value of many breeds changed over time. Relative to Hereford steers, Angus, Hereford x Angus cross, Continental cross, and low percentage Brahman steers all gained in price from 1986/87 to 1993. Longhorn Cross steers' price declined relative to Hereford steers over the same time period.
Keywords: Cattlemen& #x27; s Day; 1995; Kansas Agricultural Experiment Station contribution; no. 95-357-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 727; Beef; Feeder steer; Prices; Feeder steer characteristics; Breeds